Analysis of secondary data: Considerations revisited - Linda L Pederson; John J Koval; Evelyn Vingilis (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2022)
In a recent publication, we discussed the benefits and cautions of using secondary data analyses in research on lifestyle and health behavior [1]. We provided some guidelines about the use of secondary data in terms of the contributions that can be made and at the same time considerations necessary in using data that are collected by someone else. The use of secondary data to explore social and health issues results in being able to provide information about important issues in a timely fashion. Secondary data can answer two types of questions: descriptive and analytical [2]. Hence, the information can be used to describe events or trends or it can be used to examine relationships among variables cross-sectionally or longitudinally.